2017
DOI: 10.1016/j.cdtm.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiological survey of gallbladder carcinoma in northwestern China, 2009–2013: 2379 cases in 17 centers

Abstract: ObjectiveTo analyze the clinical epidemiological characteristics of patients with gallbladder carcinoma recruited from 17 hospitals in five northwestern provinces of China (Shaanxi Province, Gansu Province, Qinghai Province, Ningxia Hui Autonomous Region, and Xinjiang Uygur Autonomous Region) from 2009 to 2013, and to summarize the clinical diagnosis and treatment data of gallbladder carcinoma.MethodsClinical information of 2379 patients with gallbladder carcinoma from 17 hospitals in five northwestern provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 18 publications
2
25
1
2
Order By: Relevance
“…7 In agreement to present study, Shen HX et al, also reported that GBC was more prone to occur in elderly women. 13 In this study, the mean age was also comparable with most of the other reported studies, although in some studies it had been suggested that there was higher incidence of GBC with an older age. [14][15][16][17][18] A Chinese survey, has also reported higher mean age (63.7±11.3 years) as compared to present study mean age of 52.62±12.14 years.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…7 In agreement to present study, Shen HX et al, also reported that GBC was more prone to occur in elderly women. 13 In this study, the mean age was also comparable with most of the other reported studies, although in some studies it had been suggested that there was higher incidence of GBC with an older age. [14][15][16][17][18] A Chinese survey, has also reported higher mean age (63.7±11.3 years) as compared to present study mean age of 52.62±12.14 years.…”
Section: Discussionsupporting
confidence: 87%
“…[14][15][16][17][18] A Chinese survey, has also reported higher mean age (63.7±11.3 years) as compared to present study mean age of 52.62±12.14 years. 13 In the present study, most common presenting symptom of GBC was pain in right hypochondrium followed by anorexia, pruritus, weight loss and nausea and vomiting.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…When it comes to the extent of the resection, this parameter is dictated by the stage of the tumor; however, improvement of the surgical techniques in regard to liver resection and even liver transplantation as well as in regard to the perioperative management of these patients conducted to an increasing number of cases who can benefit from radical surgery for gallbladder carcinoma [14,15]. Cases presenting advanced stage disease which is no longer amenable to surgery with curative intent can also benefit from palliative procedures in order to minimize the effects of gastrointestinal or biliary obstruction [2]. In selected cases adjuvant therapies such as chemotherapy or radiotherapy might be also associated in order to improve the overall outcomes [2].…”
Section: Treatment Options In Gallbladder Carcinomamentioning
confidence: 99%
“…Gallbladder carcinoma represents the most frequently encountered malignant tumor originating from the biliary tract, with a low rate of diagnostic, a low rate of surgical treatment, and an extremely poor long-term prognostic [1,2].…”
Section: Introductionmentioning
confidence: 99%